Meningitis Tuberkulosis Pada Anak - Nadya Gratia Juliawan; Ida Ayu Putu Purnamawati (PT Kalbe Farma Tbk., 2023)
Tuberculous meningitis is extrapulmonary tuberculosis with a very high morbidity and mortality rate, especially in paediatric population. Clinicians should be able to recognize tuberculous meningitis as early as possible to provide appropriate management to reduce disabilities and death